First record of the Russian sturgeon Acipenser gueldenstaedtii Brandt & Ratzeburg, 1833 (Acipenseriformes: Acipenseridae) from Argentina - Demonte, Lucio Danilo (2017)
Acipenser gueldenstaedtii is recorded for the first time from Argentina, from lotic and lentic environments of the lower Paraná and La Plata rivers in the provinces of Santa Fe and Buenos Aires.The species has previously been mentioned as introduced to the Negro river in Uruguay. Probably all known specimens were accidentally released from aquiculture facilities located in this affluent to the Uruguay river.